INTEGRATING PROJECT-BASED LEARNING INTO ENGLISH FOR SPECIFIC PURPOSES CLASSES AT TERTIARY LEVEL: PERCEIVED CHALLENGES AND BENEFITS - Tuyen, Le Van; Tien, Ho Hai (VNU Journal of Foreign Studies; Vol 37 No 4DO - 10.25073/2525-2445/vnufs.4642, 2021)
In the last decade, EFL educators have attempted to experiment with various teaching methods to discover more effective ways of teaching and learning English, including English for Specific Purposes (ESP). Such methods as outcome-based learning (OBL), project-based learning (PBL), or cooperative learning (CBL) have received a lot of attention. Investigating the benefits and challenges of these methods in different contexts is really necessary. The current exploratory study, therefore, aimed to explore students’ perceived challenges and benefits of integrating PBL into ESP classes with the ‘English for marketing’ course designed for students majoring in Business English at Ho Chi Minh City University of Technology (HUTECH). With the participation of 64 fourth-year students and the employment of three main data collection instruments including the questionnaire, student interviews and journals, the findings of the study reveal that the integration of PBL into ESP classes has brought more benefits to the students than challenges. Specifically, they could enhance their language and content knowledge, workplace-related skills, self-responsibility and motivation. Meanwhile, they mainly encountered challenges related to classmates such as lack of skills, English proficiency, and negative attitudes. It is expected that the findings of the study would partly contribute to the existing knowledge of the study field and shed light on the role of PBL in ESP education at HUTECH in particular and at the Vietnamese tertiary level in general.